1989
DOI: 10.1007/bf00150011
|View full text |Cite
|
Sign up to set email alerts
|

Explosive events in the solar transition zone

Abstract: The properties of explosive events in the solar transition zone are presented by means of detailed examples and statistical analyses. These events are observed as regions of exceptionally high velocity (~ 100 km s 1) in profiles of C1v, formed at 102 K, observed with the High Resolution Telescope and Spectrograph (HRTS). The following average properties have been determined from observations obtained during the third rocket flight of the HRTS: full width at half maximum extent along the slit -1.6 • 103 kin; ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
157
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(166 citation statements)
references
References 10 publications
9
157
0
Order By: Relevance
“…Explosive events have been observed with high spectral and spatial resolutions by HRTS and SUMER (cf., Dere et al 1989b;Kjeldseth-Moe and Cheng 1994;Moses et al 1994;Innes et al 1997aInnes et al , 1997bInnes 2001). Observations of the line profile of C IV at 154.8 nm with HRTS revealed that, in general, the shapes of the line during the events can be described by three Gaussian profiles with one component at rest and the others shifted by ≈10 pm to either red or blue (Dere et al 1981).…”
Section: Explosive Eventsmentioning
confidence: 96%
“…Explosive events have been observed with high spectral and spatial resolutions by HRTS and SUMER (cf., Dere et al 1989b;Kjeldseth-Moe and Cheng 1994;Moses et al 1994;Innes et al 1997aInnes et al , 1997bInnes 2001). Observations of the line profile of C IV at 154.8 nm with HRTS revealed that, in general, the shapes of the line during the events can be described by three Gaussian profiles with one component at rest and the others shifted by ≈10 pm to either red or blue (Dere et al 1981).…”
Section: Explosive Eventsmentioning
confidence: 96%
“…Dere et al (1989) already noted "... the lack of detectable apparent motions of such high-velocity events". Innes (2004) again mention this conflict that is still unsolved.…”
Section: Introductionmentioning
confidence: 99%
“…In spectroscopic data EEs are easily detected by the redshift and blueshift of the observed transition region (TR) line. The terminology "explosive event" has first been introduced by Dere et al (1984) based on the analysis of high-resolution spectra of TR emission lines obtained by the HRTS instrument on Spacelab, but it turned out that this term is quite debatable (e.g., Dere et al 1989) and may be misleading.With the advent of SoHO-SUMER (Wilhelm et al 1995) began a revival of this field of research. Typical EEs were found to be short-lived (60 s to 200 s), small-scale (1500 km to 2500 km), high-velocity (±50 km s −1 to ±150 km s −1 ) flows that occur very frequently, sometimes in bursts.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the explosive events were studied by Brueckner & Bartoe (1983), Dere et al (1989), Porter & Dere (1991), Innes et al (1997Innes et al ( , 2001), Chae et al (1998), Pérez et al (1999), Teriaca et al (2001), and Teriaca et al (2002).…”
Section: Introductionmentioning
confidence: 99%